Cavanaugh justice : serial affair - Ferrarella, Marie (Ferrarella, Marie. Cavanaugh justice., 2022)
"Small-town detective Liberty Lawrence is hot on the trail of a serial killer. And this case is as personal as they come. So when the criminal's body count moves to California, Liberty follows--and joins forces with lawman Campbell Cavanaugh. With chemistry as explosive as the danger surrounding them, though, the duo is racing against time before the killer turns on Liberty herself?"--Amazon.com.